Adaptation of Migrant Workers' Child in Cianjur Regency, Indonesia - Yana Sundayani; Adi Fahrudin; Binahayati R. Nunung Nurwati (Asian Social Work Journal, 2018)
The study aims to examine empirically in depth the adaptation of children of migrant workers aged 13 to 17 years whose parents, fathers or mothers work abroad as domestic migrant workers. The study used a qualitative approach with data collection techniques to interview and observe informants, as well as conduct study studies from various documentation. Determination of four informants using purposive techniques. This study looks at the adaptation of four sub-aspects namely the pattern used; rules or norms applied; and changes in child behavior of migrant workers. The results of the empirical study are then analyzed so that it is known the ability and flexibility of migrant workers' children in dealing with environmental changes that occur; and known factors that support in adaptation.